48‐4: Invited Paper: High‐resolution Integral Imaging 3D Display System. Issue 1 (28th June 2021) - Zhang, Han-Le; Ren, Hui; Xing, Yan; Xia, Yun-Peng; Li, Shuang; Deng, Huan; Wang, Qiong-Hua
Abstract : A high‐resolution integral imaging 3D display system without color moiré pattern and graininess is proposed. The system consists of a 2D display, a micro‐lens array, a holographic diffuser, and a transmissive mirror device. The experimental results prove the feasibility of the proposed system.